Association between SOX2 and OCT4 expression and the chemoradiation therapeutic response in undifferentiated non-keratinizing nasopharyngeal carcinoma (Medical Journal of Indonesia, 2020)
BACKGROUND Self-renewal ability of cancer stem cells (CSS) is one of the possible causes for nasopharyngeal carcinoma (NPC) to relapse and metastasize. SOX2 and OCT4 are markers for expression of the embryonic stem cells and crucial for the progression of various malignancies. This study was aimed to analyze the association between SOX2 and OCT4 expression and chemoradiation therapeutic response in undifferentiated non-keratinizing NPC. METHODS This cross-sectional study used archival data from Department of Anatomical Pathology, Faculty of Medicine, Universitas Indonesia, Cipto Mangunkusumo Hospital from January 2014 to December 2016. The outcomes were classified into good-response (complete and partial response) and poor-response groups (progressive and stable disease) based on response evaluation criteria in solid tumors (RECIST). SOX2 and OCT4 immunohistochemistry staining was performed using the initial specimen (before chemoradiation therapy) and positively expressing tumor cells were counted. Staining intensity was graded as: strong, moderate, weak, and negative. Strong and moderate staining was considered positive expression. RESULTS 33 males and 8 females were included; 48% were ≥50 years old. Most of the patients had stage IV (n = 35) and several patients had stage II (n = 3) and III (n = 3). More cells expressed OCT4 in the good-response group than the poor-response group (61.3% versus 37.0%, p = 0.009). Meanwhile, there were less cells expressing SOX2 in the good-response group than the poor-response group (36.3% versus 61.1%, p = 0.097). CONCLUSIONS This study suggests that OCT4 is a potential predictive marker for therapeutic response in patients with NPC.